2009
DOI: 10.1038/ajh.2008.326
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Exposure to Gestational Diabetes, Child Adiposity, and Blood Pressure

Abstract: Background Intrauterine exposure to gestational diabetes mellitus (GDM) may promote offspring obesity and higher systolic blood pressure (SBP) by adolescence. Few studies have examined adiposity or SBP in younger children exposed to GDM. This study’s objective was to examine associations of maternal glucose tolerance during pregnancy with offspring adiposity and SBP at age 3 years. Methods We studied 1,238 mother-child pairs in Project Viva, a prospective prebirth cohort study. Exposures were maternal blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
181
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(207 citation statements)
references
References 35 publications
20
181
3
1
Order By: Relevance
“…Consequently, the long-term effects of diabetes during pregnancy on later childhood health such as obesity/adiposity, mainly via large for gestational age at birth, has been clearly established. [13][14][15] In contrast, data regarding the longterm effects of maternal diabetes during pregnancy on the offspring's cognitive development are relatively limited and, when data are available, the findings are inconclusive. [16][17][18][19][20][21][22][23] The mechanisms by which maternal diabetes during pregnancy is associated with the offspring's cognitive development are unclear.…”
mentioning
confidence: 86%
“…Consequently, the long-term effects of diabetes during pregnancy on later childhood health such as obesity/adiposity, mainly via large for gestational age at birth, has been clearly established. [13][14][15] In contrast, data regarding the longterm effects of maternal diabetes during pregnancy on the offspring's cognitive development are relatively limited and, when data are available, the findings are inconclusive. [16][17][18][19][20][21][22][23] The mechanisms by which maternal diabetes during pregnancy is associated with the offspring's cognitive development are unclear.…”
mentioning
confidence: 86%
“…Seven studies provided BP in offspring of mothers with GDM [24,25,29,34,36,39,40], and two in offspring of mothers with type 1 diabetes [32,33]. Four studies included pooled outcome data for offspring of both type 1 diabetes and GDM mothers [28,30,38,42]; one study included data from prepregnancy type 2 diabetes in their pooled diabetic group [28]; authors provided separate data for type 1 diabetes and GDM for three studies [30,38,42].…”
Section: Literature Searchmentioning
confidence: 99%
“…Five studies reported maternal prepregnancy BMI [25,30,36,39,40], and two studies reported offspring SBP data adjusted for prepregnancy maternal BMI [38,39]. A description of studies included is provided in Table 1.…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations